2020
DOI: 10.1098/rspb.2019.2497
|View full text |Cite
|
Sign up to set email alerts
|

Continent-wide effects of urbanization on bird and mammal genetic diversity

Abstract: Urbanization and associated environmental changes are causing global declines in vertebrate populations. In general, population declines of the magnitudes now detected should lead to reduced effective population sizes for animals living in proximity to humans and disturbed lands. This is a cause for concern because effective population sizes set the rate of genetic diversity loss due to genetic drift, the rate of increase in inbreeding and the efficiency with which selection can act on beneficial alleles. We p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 58 publications
3
120
2
Order By: Relevance
“…We also corrected elevation range for potential 419 biases introduced by species range area, because larger ranges tended to encompass greater 420 topographical heterogeneity. Human population sizes were recorded for each site in the 421 aforementioned genetic diversity database (Schmidt et al 2020a). 422…”
Section: Data Assembly 388mentioning
confidence: 99%
“…We also corrected elevation range for potential 419 biases introduced by species range area, because larger ranges tended to encompass greater 420 topographical heterogeneity. Human population sizes were recorded for each site in the 421 aforementioned genetic diversity database (Schmidt et al 2020a). 422…”
Section: Data Assembly 388mentioning
confidence: 99%
“…Therefore, we consider country size to make population density values comparable between countries, as well as geography since islands and the mainland are subject to different levels of anthropogenic impact and extinction dynamics [26]. Similarly, the impacts of urbanization are assumed to have an overall detrimental effect on biodiversity, which is also strongly related to the size and density of human populations [27][28][29]. Further, since socio-economic aspects, such as educational level and income, also modulate people's interaction with the environment [30,31], we included the following variables: GDP, % of the GDP invested in education, and USD invested in education.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In addition, it was reported that even more of Earth's land surface (approximately 75%) has been modified by humans to support urban residences [5]. This human-induced land cover change has caused considerable global climate change, environmental pollution, and biodiversity loss [6], and has also led to air pollution in urban areas and subsequent health problems for urban residents [3,7]. As such, a deeper understanding of the spatial mechanisms of urbanization is more important than ever.…”
Section: Introductionmentioning
confidence: 99%